Interventions for hidradenitis suppurativa: a Cochrane systematic review incorporating GRADE assessment of evidence quality. (30th March 2016) - Ingram, J.R.; Woo, P.N.; Chua, S.L.; Ormerod, A.D.; Desai, N.; Kai, A.C.; Hood, K.; Burton, T.; Kerdel, F.; Garner, S.E.; Piguet, V.
Summary: More than 50 interventions have been used to treat hidradenitis suppurativa (HS), and so therapy decisions can be challenging. Our objective was to summarize and appraise randomized controlled trial (RCT) evidence for HS interventions in adults. Searches were conducted in Medline, Embase, CENTRAL, LILACS, five trials registers and abstracts from eight dermatology conferences until 13 August 2015. Two review authors independently assessed study eligibility, extracted data and assessed methodological quality. Primary outcomes were quality of life and adverse effects of the interventions. Twelve trials, from 1983 to 2015, investigating 15 different interventions met our inclusion criteria. The median trial duration was 16 weeks and the median number of participants was 27. Adalimumab 40 mg weekly improved the Dermatology Life Quality Index (DLQI) by 4·0 points, which equates to the minimal clinically important difference for the scale, compared with placebo (95% confidence interval −6·5 to −1·5 points). Evidence quality was reduced to 'moderate' because the results are based on only a single study. Adalimumab 40 mg every other week was ineffective in a meta‐analysis of two studies comprising 124 participants. Infliximab 5 mg kg −1 improved the DLQI score by 8·4 points after 8 weeks in a moderate‐quality study completed by 33 of 38 participants. Etanercept 50 mg twice weekly was ineffective. Inclusion of a gentamicin sponge prior to primary closure did not improve outcomes. Other interventions, including topical and oral antibiotics, were investigated by relatively small studies, preventing treatment recommendations due to imprecision. More, larger RCTs are required to investigate most HS interventions, particularly oral treatments and surgical therapy. Moderate‐quality evidence suggests that adalimumab given weekly and infliximab are effective, whereas adalimumab every other week is ineffective. Abstract : What's already known about this topic? Many interventions have been tried for hidradenitis suppurativa (HS). Evidence supporting the choice of intervention for HS is often limited. What does this study add? Moderate‐quality evidence suggests that adalimumab given weekly and infliximab are effective, whereas adalimumab every other week is ineffective. There are very limited or no randomized controlled trial data in HS for antibiotic therapy, retinoids, oral immunomodulators or the timing and type of surgery to perform. Linked Comment: Blok. Br J Dermatol 2016;174 : 953–954